Effects of different size of fly ash as cement replacement on self-compacting concrete properties - Dilan Rantung; Steve W.M. Supit; Seska Nicolaas (Fakultas Teknik Universitas Sam Ratulangi, 2019)
This paper aims to investigate experimentally the influence of replacing cement with different fineness of fly ash based on flowability, passing ability, compressive strength, tensile strength (splitting). Concretes with 15% fly ash (passed a number 100 sieve) and fine fly ash (passed a number 200 sieve) as cement replacement were cast and tested at 7, 14, 28 days after water curing. A superplasticizer in the form of viscocrete 3115 N was constantly used for each concrete mixtures as much as 1% by weight of cement. The results show that the use of fly ash does not significantly increased the compressive strength and tensile strength of SCC mixtures. However, concrete with 15% fine fly ash its self and combined 7.5% fly ash with 7.5% fine fly ash show better flowability and passing ability when compared to concrete with cement only indicating the performance of using smaller particle sizes of fly ash could lead better properties of SCC that can be potentially used for building construction application.